Business ethics, Corporate Good Citizenship and the Corporate Social Policy Process: A view from the United States - Epstein, Edwin M. (Journal of business ethics, 1989)
Within the American context, the term Corporate Good Citizenship, a rather vague and somewhat dated notion, bears little relationship to the concept of Business Ethics. Whereas the latter refers to systematic reflection on the moral significance of the institutions, policies and behavior of business actors in the normal course of their business operations, the former is a subset of the broader notion of Corporate Social Responsibility and denotes, generally, discretionary, possibly altruistic, “non-business” relationships between business organizations and diverse community stakeholders. A newer concept, the Corporate Social Policy Process, which focuses on the institutionalization within business organizations of processes facilitating individual and organizational reflection and choice regarding the moral significance of personal and organizational action together with a consideration of the likely consequences of such action, provides analytical linkages between Business Ethics and Corporate Good Citizenship which can be useful to business scholars and operating managers alike. Specific aspects of Corporate Good Citizenship, including corporate community involvements, are examined and particular attention is paid to current trends in corporate donations, including an increasing emphasis on “strategic philanthropy” which explicitly mixes practical and benevolent motives in company giving policies and practices.